A microwave non-destructive testing method for controlling polymeric coating of metal layers in industrial products. (March 2019) - Mazzinghi, A.; Freni, A.; Capineri, L.
Abstract: The paper exploits the possibility of extracting the geometric properties of a polymeric coating of periodic metal layers used in industrial products from non-contact microwave backscattering measurements. Specifically, a flexible pipe having a periodically corrugated metal profile coated with a thick Polivinylidenedifluoride (PVDF) layer, suitable for oil industry applications, has been considered. The combined use of magnitude and phase of the reflected signal, acquired on a wide relative frequency band (∼15%), allows calculating the dielectric filling level and the period of each corrugation with accuracy better than 1/100 of the period length, 21 mm in our case. The results of an experimental campaign, carried out to estimate the accuracy achievable in the operational environment, are also shown.